2017
DOI: 10.1002/mds.27028
|View full text |Cite
|
Sign up to set email alerts
|

The current state of postoperative imaging in the presence of deep brain stimulation electrodes

Abstract: For more than a decade, medically refractory movement disorders have been treated with deep brain stimulation (DBS) devices. Bilateral DBS of the subthalamic nucleus (STN), globus pallidus, and thalamus have been effective in reducing the complications of medications in later-stage movement disorder patients. However, the effectiveness of the DBS device is highly dependent on the proper radiologic and electrophysiological identification of DBS target structures and the accurate placement of the DBS electrodes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Owing to its anatomical intricacy, MRI of the subcortex only lends support by using high-field MRI (3 T or higher). Hence, because of imprecise electrode placement (e.g., Gilmore et al, 2017 ) due to the use of preoperative low field structural MRI images, electrode placement planning may lead to unknown electrical fields in brain tissue and hamper an optimal clinical outcome. Meanwhile, computational models have supported the advance of DBS technology (e.g., Butson et al, 2006 ; Miocinovic et al, 2006 ; Gunalan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its anatomical intricacy, MRI of the subcortex only lends support by using high-field MRI (3 T or higher). Hence, because of imprecise electrode placement (e.g., Gilmore et al, 2017 ) due to the use of preoperative low field structural MRI images, electrode placement planning may lead to unknown electrical fields in brain tissue and hamper an optimal clinical outcome. Meanwhile, computational models have supported the advance of DBS technology (e.g., Butson et al, 2006 ; Miocinovic et al, 2006 ; Gunalan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) is a neurosurgical procedure where electrical stimulation is delivered to specific subcortical targets in the brain, providing therapeutic benefits to patients with movement disorders and other neurological diseases [ 1 ]–[ 4 ]. For patients with implanted DBS systems, magnetic resonance imaging (MRI) is highly useful, allowing for postoperative monitoring, target verification, and localization of the electrodes [ 5 ], [ 6 ], along with elucidating the functional effects of stimulation on affected brain networks [ 7 ]. As the field of DBS therapy advances, the need for application of higher field strength MRI (i.e., 3 T and above) for improved contrast-to-noise ratio is increasingly imperative [ 8 ], [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existing postoperative DBS MRI literature has largely focused on evaluation of procedure safety ( 19 22 ), electrode mapping and clinical correlates ( 7 , 23 , 24 ), functional connectivity ( 25 ), electrode artifact ( 26 , 27 ), and imaging findings such as symptomatic hemorrhage and edema ( 28 33 ). To date, there has been no comprehensive evaluation of postoperative radiographic abnormalities using MRI nor comparison of sequences best suited for detecting these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, a number of studies have demonstrated that postoperative MRI can be safely performed in DBS patients at 1.5 T and 3.0 T if specific, restricted conditions are met during scanning (14)(15)(16)(17)(18). These promising safety data have allowed for the incorporation and study of postoperative MRI in the care of DBS patients (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%